Bloch Equations Versus Balance Equation: From F. Bloch to A. Einstein - Astapenko, V.A.; Mutafyan, M.I. (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2022)
We investigate the correspondence between balance equation for population inversion of Two-Level System (TLS) and equations for optical Bloch vector which describe the interaction of electromagnetic field and TLS. Based on an analytical treatment, the condition for such a correspondence is established and an expression is obtained for the rate of the radiative transition. Particularly, the problem of applicability of the perturbation theory when writing the balance equation, which also describes a strong change in the population inversion, is resolved.